La isla del tesoro Based on a Novel by Robert L. Stevenson - Heston, Fraser Clarke; Steadman, Robert; Heston, Charlton; Bale, Christian; Reed, Oliver; Lee, Christopher; Glover, Julian; Postlethwaite, Pete (Warner, 2011)
Filmed many, many times before by numerous filmmakers for theatrical and TV venues, by 1989 there were no shortages of "Treasure Island" productions, but Fraser Heston wanted to be faithful to novel, vividly evoking the period by referencing the paintings of N.C. Wyeth, and going for a grittier look with performances that illustrated the nastier side of pirates. The film remained PG-friendly, but edgier than prior versions, and the screenwriting avoided some of the linguistic and archetypal clichés that made lead villain Long John Silver a caricature in prior films, instead of a scheming, sly S.O.B. deserving the hangman's noose. Filmed in Cornwall, England, and parts of Jamaica, "Treasure Island" also boasted a perfect cast. Oliver Reed, even when unintelligible, is perfect as the rum-marinated Billy Bones who brings the treasure map to young Jim Hawkins (Christian Bale, fresh from "Empire of the Sun"); Christopher Lee is chilling as Blind Pew; and Charlton Heston does a fine job as Silver, giving the character dimensions implied in the novel, but rubbed out in prior film versions. [www.kqek.com]
Keywords: DVD-Video